A kind of nano ceramic slurry and preparation method thereof
By preparing nanoceramic slurry, the modified carbon nanotubes are solved by using potassium permanganate carbon oxide nanotubes, lithium tetrahydrogen aluminum tetrahydrogen acetate reactions, and copolymerization with other materials. In the problem of insufficient strength and durability in special application scenarios, efficient crack resistance, compression resistance and durability are achieved.
Patent Information
- Application Number
- CN202410980584.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-07-22
AI Technical Summary
Existing concrete materials are difficult to meet the strength and durability requirements in special application scenarios, especially in subway tunnels, super high-rise buildings, high-speed railways and cross-sea bridges.
Prepare a nanoceramic slurry, and oxidize the carbon nanotubes through potassium permanganate and sulfuric acid solutions, and then reduce with lithium tetrahydrogenomic acid to obtain hydroxylated carbon nanotubes and react with allyl chloroacetate to form modified carbon Nanotubes. Then, carbon nanotube polycarboxylic acid subtracted by reaction of acrylic acid, 3-methylbut-3-enyl polyethylene glycol ether, gamma-methacryloyloxypropyltrimethoxysilane and modified carbon nanotubes were prepared by reaction of carbon nanotubes. The aqueous agent is mixed with silicate cement, sand and gravel and spherical porous nanoalumina to make a nanoceramic slurry.
Nanoceramic slurries perform excellently in crack resistance, compressive resistance and durability, which can significantly improve the strength and durability of concrete, and are suitable for high-demand construction and civil engineering applications.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of construction, in particular to a nano ceramic slurry and a preparation method thereof. Background Art
[0002] At present, concrete is one of the most widely used materials for construction and civil engineering. With the development of economy and technology, the application scope of concrete has expanded to subway tunnels, super high-rise buildings, high-speed railways, cross-sea bridges, etc. These special application scenarios have put forward new requirements for the strength and durability of concrete.
[0003] Therefore, the present invention prepares a nano ceramic slurry with excellent crack resistance, compression resistance and durability. Summary of the invention
[0004] The purpose of the present invention is to provide a nano ceramic slurry and a preparation method thereof to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A nano ceramic slurry is characterized in that the nano ceramic slurry is obtained by mixing silicate cement, sand and gravel, spherical porous nano alumina and carbon nanotube polycarboxylic acid water reducer.
[0007] As an optimization, the spherical porous nano-alumina is obtained by drying and calcining aluminum isopropoxide gel.
[0008] As an optimization, the carbon nanotube polycarboxylic acid water reducer is obtained by reacting acrylic acid, 3-methylbut-3-enyl polyethylene glycol ether, γ-methacryloxypropyltrimethoxysilane and modified carbon nanotubes.
[0009] As an optimization, the modified carbon nanotubes are obtained by oxidizing the carbon nanotubes with potassium permanganate and sulfuric acid solution, reducing them with lithium aluminum tetrahydride, and then reacting with allyl chloroacetate.
[0010] As an optimization, the carbon nanotube model is LBW-5585, which comes from Hubei Langbowan Biotechnology Co., Ltd.
[0011] A method for preparing a nano-ceramic slurry comprises the following steps:
[0012] (1) Mix carbon nanotubes and sulfuric acid solution with a mass fraction of 4.6-4.8% in a mass ratio of 1:(55-65), ultrasonically disperse for 25-35 minutes, stir in an oil bath at 800-900 r / min to 145-155°C, add the mixed solution with a mass fraction of 62-63 times the mass of carbon nanotubes at a uniform rate within 30-40 minutes, continue stirring for 4-6 hours, cool naturally to room temperature and filter, add hydrochloric acid solution with a mass fraction of 23-25% with a mass fraction of 25-35 times the mass of carbon nanotubes, let stand for 4-6 minutes and filter, and remove The oxidized carbon nanotubes are washed with deionized water for 3 to 5 times, and dried at 75 to 85° C. for 11 to 13 hours to obtain oxidized carbon nanotubes; the oxidized carbon nanotubes, lithium aluminum tetrahydride and tetrahydrofuran are mixed in a mass ratio of 1: (0.3 to 0.4): (70 to 80), stirred at 800 to 900 r / min for 10 to 14 hours at 15 to 25° C. and 800 to 900 r / min in a nitrogen environment, and naturally cooled to room temperature, and then washed with tetrahydrofuran, a hydrochloric acid solution with a mass fraction of 3 to 4% and deionized water for 3 to 5 times, respectively, and dried at 75 to 85° C. for 10 to 14 hours to obtain hydroxylated carbon nanotubes;
[0013] (2) Hydroxylated carbon nanotubes, pyridine and N,N-dimethylformamide were mixed in a mass ratio of
[0014] 1: (0.01-0.02): (16-17) mixed, stirred at 100-200 rpm for 10-20 min at 20-30 ° C under nitrogen atmosphere, added 3-4 times the mass of allyl chloroacetate of hydroxylated carbon nanotubes, continued stirring for 25-35 min, heated to 35-45 ° C and continued stirring for 1-3 h, filtered, washed with N, N-dimethylformamide 3-5 times, dried at 75-85 ° C for 3-4 h, to obtain modified carbon nanotubes;
[0015] (3) 3-methylbut-3-enyl polyethylene glycol ether, γ-methacryloxypropyltrimethoxysilane and deionized water are mixed in a mass ratio of 1:(0.6-0.8):(5-7), stirred at 35-45° C. and 100-200 rpm for 25-35 min, and in a nitrogen atmosphere, a mixed monomer solution of 13-15 times the mass of 3-methylbut-3-enyl polyethylene glycol ether and an oxidant solution of 0.7-0.9 times the mass of 3-methylbut-3-enyl polyethylene glycol ether are uniformly added dropwise within 20-40 min, and the mixture is kept warm for 1-3 h and then naturally cooled to room temperature, and a sodium hydroxide solution with a mass fraction of 31-33% is added to adjust the pH to 4-6, and the mixture is allowed to stand for 35-45 min, and washed with deionized water and anhydrous ethanol for 3-5 times respectively, and dried at 35-45° C. for 8-10 h to obtain a carbon nanotube polycarboxylic acid water reducer;
[0016] (4) Aluminum isopropoxide and deionized water are mixed in a mass ratio of 1:(2.1-2.3), stirred at 80-90°C and 100-200 rpm for 25-35 min, 0.37-0.39 times the mass of aluminum isopropoxide and a 60-70% nitric acid solution and 0.1-0.3 times the mass of aluminum isopropoxide are added, the temperature is raised to 95-105°C, stirring is continued for 6-8 hours, distilled for 20-30 minutes, a ball is dropped into an oil ammonia column with a disposable dropper, the ball is poured out after standing for 2-3 hours, washed with isopropanol 3-5 times, dried at 20-30°C for 23-25 hours, dried at 105-115°C for 7-9 hours, moved to a muffle furnace, heated to 550-650°C at a rate of 2-4°C / min, calcined for 3-5 hours, cooled naturally to room temperature, ground and sieved with 200-300 mesh, and spherical porous nano-alumina is obtained;
[0017] (5) Mix silicate cement and sand in a mass ratio of 1:(2-4), stir at 20-30°C and 55-65rpm for 1-3min, add 0.02-0.04 times the mass of silicate cement spherical porous nano-alumina and 0.001-0.002 times the mass of silicate cement polyethylene glycol with a mass fraction of 0.4-0.6%, continue stirring for 1-3min, add 0.03-0.05 times the mass of silicate cement carbon nanotube polycarboxylate water reducer and 0.4-0.5 times the mass of silicate cement deionized water, continue stirring at 500-600rpm for 10-20min, let stand for 1-3min, and obtain nano ceramic slurry.
[0018] As an optimization, the mixed solution in step (1) is obtained by mixing potassium permanganate and a sulfuric acid solution with a mass fraction of 4.6-4.8% in a mass ratio of 1:(23-25), and ultrasonically dispersing for 25-35 minutes.
[0019] As an optimization, the reaction equation for hydroxylating carbon nanotubes in step (1) is:
[0020]
[0021] As an optimization, the reaction equation for modifying the carbon nanotubes in step (2) is:
[0022]
[0023] As an optimization, the mixed monomer solution in step (3) is obtained by mixing acrylic acid, modified carbon nanotubes, ascorbic acid, mercaptoethanol and deionized water in a mass ratio of 1:(2-3):(0.01-0.02):(0.003-0.005):(3-5).
[0024] As an optimization, the oxidant solution in step (3) is obtained by mixing ammonium persulfate and deionized water in a mass ratio of 1:(4-6).
[0025] As an optimization, the liquid paraffin in step (3) is of model N / A and is from Hubei Xinyuhong Biotechnology Co., Ltd.
[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0027] When preparing nano ceramic slurry, the present invention comprises the following steps: oxidizing carbon nano tubes with potassium permanganate and sulfuric acid solution, and then reducing with lithium aluminum tetrahydride to obtain hydroxylated carbon nano tubes; reacting hydroxylated carbon nano tubes with allyl chloroacetate to obtain modified carbon nano tubes; reacting acrylic acid, 3-methylbut-3-enyl polyethylene glycol ether, gamma-methacryloxypropyltrimethoxysilane and modified carbon nano tubes to obtain carbon nano tube polycarboxylic acid water reducer; drying and calcining aluminum isopropoxide after gelling to obtain spherical porous nano alumina; and finally mixing silicate cement, sand and gravel, spherical porous nano alumina and carbon nano tube polycarboxylic acid water reducer to prepare nano ceramic slurry.
[0028] Firstly, the carbon nanotubes are oxidized by potassium permanganate and sulfuric acid solution, and then reduced by lithium aluminum tetrahydride to obtain hydroxylated carbon nanotubes; the hydroxylated carbon nanotubes are reacted with allyl chloroacetate to obtain modified carbon nanotubes; the carbon nanotubes are oxidized by potassium permanganate and sulfuric acid solution, and then reduced by lithium aluminum tetrahydride to reduce the carboxyl groups on the surfaces of the oxidized carbon nanotubes to hydroxyl groups, thereby improving the subsequent grafting efficiency of allyl chloroacetate, so as to perform in-situ polymerization on the carbon nanotubes to generate polycarboxylic acid organic macromolecules, enhance the dispersibility and dispersion stability of the carbon nanotubes, and improve the crack resistance of the nano-ceramic slurry.
[0029] Secondly, acrylic acid, 3-methylbut-3-enyl polyethylene glycol ether, γ-methacryloxypropyltrimethoxysilane and modified carbon nanotubes are reacted to obtain carbon nanotube polycarboxylic acid water reducer; aluminum isopropoxide is dried and calcined after gelation to obtain spherical porous nano alumina; silicate cement, sand and gravel, spherical porous nano alumina and carbon nanotube polycarboxylic acid water reducer are then mixed to prepare nano ceramic slurry; γ-methacryloxypropyltrimethoxysilane is introduced for copolymerization reaction, which increases the adsorption amount of water reducer molecules in the nano ceramic slurry, reduces the permeability and water absorption rate of the nano ceramic slurry, and improves the durability of the nano ceramic slurry; doping with spherical porous nano alumina can fill the pores in the slurry, improve the microstructure of the slurry, and enhance the compressive strength and durability of the nano ceramic slurry through the strengthening effect. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the nano-ceramic slurry prepared in the following examples:
[0032] Crack resistance: The nano-ceramic slurry obtained in each embodiment and the comparative example were stirred evenly and poured into a mold of 800mm*600mm*100mm respectively, vibrated 3 times with a vibration table, placed in a standard curing box for curing for 1 day, and then demolded. The molds were cured in a 50°C steam curing box for 28 days and then taken out. The splitting tensile strength was tested according to GB / T50081.
[0033] Compressive performance: The nano-ceramic slurry obtained in each embodiment and the comparative example were stirred evenly and poured into 30mm*30mm*30mm molds respectively, vibrated 3 times with a vibration table, placed in a standard curing box for curing for 1 day, and then demolded. The molds were cured in a 50°C steam curing box for 7 days and then taken out. The compressive strength was tested according to GB / T50081.
[0034] Durability: The nano-ceramic slurry obtained in each embodiment and the comparative example were stirred evenly and poured into a 100mm*100mm*100mm mold respectively, vibrated 3 times with a vibration table, placed in a standard curing box for curing for 1 day, and then demolded. The slurry was cured in a 50°C steam curing box for 28 days and taken out. According to GB / T50082, 100 freeze-thaw cycles were performed to test the relative dynamic modulus loss rate.
[0035] Example 1
[0036] A method for preparing a nano-ceramic slurry, the method comprising the following steps:
[0037] (1) Potassium permanganate and 4.6% sulfuric acid solution were mixed at a mass ratio of 1:23, and ultrasonically dispersed for 25 minutes to obtain a mixed solution; carbon nanotubes and 4.6% sulfuric acid solution were mixed at a mass ratio of 1:55, and ultrasonically dispersed for 25 minutes, and stirred at 800 r / min in an oil bath to 145°C, and the mixed solution with a mass of 62 times that of the carbon nanotubes was added at a uniform rate within 30 minutes, and the stirring was continued for 6 hours. After naturally cooling to room temperature, the mixture was filtered, and 25 times the mass of the carbon nanotubes was added. The mixture was stirred at 15°C and 800r / min for 14 hours under a nitrogen atmosphere, and then washed with tetrahydrofuran, a 3% hydrochloric acid solution and deionized water for 3 times, and dried at 75°C for 14 hours to obtain hydroxylated carbon nanotubes;
[0038] (2) Mix hydroxylated carbon nanotubes, pyridine and N,N-dimethylformamide in a mass ratio of 1:0.01:16, stir at 20°C and 100 rpm for 20 min under a nitrogen atmosphere, add allyl chloroacetate 3 times the mass of the hydroxylated carbon nanotubes, continue stirring for 35 min, heat to 35°C and continue stirring for 3 h, filter, wash with N,N-dimethylformamide 3 times, and dry at 75°C for 4 h to obtain modified carbon nanotubes;
[0039] (3) acrylic acid, modified carbon nanotubes, ascorbic acid, mercaptoethanol and deionized water were mixed in a mass ratio of 1:2:0.01:0.003:3 to obtain a mixed monomer solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:4 to obtain an oxidant solution; 3-methylbut-3-enyl polyethylene glycol ether, γ-methacryloxypropyltrimethoxysilane and deionized water were mixed in a mass ratio of 1:0.6:5, and stirred at 35°C and 100 rpm for 35 min. Under a nitrogen atmosphere, a mixed monomer solution of 13 times the mass of 3-methylbut-3-enylpolyethylene glycol ether and an oxidant solution of 0.7 times the mass of 3-methylbut-3-enylpolyethylene glycol ether were uniformly added dropwise within 20 minutes, and the mixture was naturally cooled to room temperature after being kept warm for 3 hours. A 31% sodium hydroxide solution was added to adjust the pH to 4, and the mixture was filtered after standing for 35 minutes. The mixture was washed with deionized water and anhydrous ethanol for 3 times respectively, and dried at 35°C for 10 hours to obtain a carbon nanotube polycarboxylic acid water reducer.
[0040] (4) Aluminum isopropoxide and deionized water were mixed at a mass ratio of 1:2.1, stirred at 80°C and 100 rpm for 35 min, 0.37 times the mass of aluminum isopropoxide and 60% nitric acid solution and 0.1 times the mass of aluminum isopropoxide were added, the temperature was raised to 95°C, stirring was continued for 8 h, distilled for 30 min, a ball was dropped into an oil ammonia column with a disposable dropper, the ball was poured out after standing for 2 h, washed with isopropanol 3 times, dried at 20°C for 25 h, dried at 105°C for 9 h, moved to a muffle furnace, heated to 550°C at a rate of 2°C / min, calcined for 5 h, cooled naturally to room temperature, ground and sieved through 200 mesh to obtain spherical porous nano-alumina;
[0041] (5) Mix silicate cement and sand in a mass ratio of 1:2, stir at 20°C and 55 rpm for 3 min, add spherical porous nano-alumina (0.02 times the mass of silicate cement) and polyethylene glycol (0.4% by mass) (0.001 times the mass of silicate cement), continue stirring for 3 min, add carbon nanotube polycarboxylate water-reducing agent (0.03 times the mass of silicate cement) and deionized water (0.4 times the mass of silicate cement), continue stirring at 500 rpm for 20 min, and let stand for 3 min to obtain nano-ceramic slurry.
[0042] Example 2
[0043] A method for preparing a nano-ceramic slurry, the method comprising the following steps:
[0044] (1) Potassium permanganate and 4.7% sulfuric acid solution were mixed at a mass ratio of 1:24, and ultrasonically dispersed for 30 minutes to obtain a mixed solution; carbon nanotubes and 4.7% sulfuric acid solution were mixed at a mass ratio of 1:60, and ultrasonically dispersed for 30 minutes, stirred at 850 r / min in an oil bath to 150° C., and 62.5 times the mass of the carbon nanotubes were added to the mixed solution at a constant rate within 35 minutes, and the stirring was continued for 5 hours. After naturally cooling to room temperature, the mixture was filtered, and 30 times the mass of the carbon nanotubes were added. A 24% hydrochloric acid solution was allowed to stand for 5 minutes, then filtered, washed with deionized water for 4 times, and dried at 80°C for 12 hours to obtain oxidized carbon nanotubes; the oxidized carbon nanotubes, lithium aluminum tetrahydride and tetrahydrofuran were mixed in a mass ratio of 1:0.35:75, stirred at 20°C and 850r / min for 12 hours under a nitrogen environment, cooled naturally to room temperature, washed with tetrahydrofuran, a 3.5% hydrochloric acid solution and deionized water for 4 times, and dried at 80°C for 12 hours to obtain hydroxylated carbon nanotubes;
[0045] (2) Mix hydroxylated carbon nanotubes, pyridine and N,N-dimethylformamide in a mass ratio of 1:0.015:16.5, stir for 15 min at 25 ° C and 150 rpm under a nitrogen atmosphere, add allyl chloroacetate (3.5 times the mass of hydroxylated carbon nanotubes), continue stirring for 30 min, heat to 40 ° C and continue stirring for 2 h, filter, wash with N,N-dimethylformamide 4 times, and dry at 80 ° C for 3.5 h to obtain modified carbon nanotubes;
[0046] (3) acrylic acid, modified carbon nanotubes, ascorbic acid, mercaptoethanol and deionized water were mixed in a mass ratio of 1:2.5:0.015:0.004:4 to obtain a mixed monomer solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:5 to obtain an oxidant solution; 3-methylbut-3-enyl polyethylene glycol ether, γ-methacryloxypropyltrimethoxysilane and deionized water were mixed in a mass ratio of 1:0.7:6, and stirred at 40°C and 150 rpm for 30 min. n, under a nitrogen atmosphere, a mixed monomer solution of 14 times the mass of 3-methylbut-3-enylpolyethylene glycol ether and an oxidant solution of 0.8 times the mass of 3-methylbut-3-enylpolyethylene glycol ether were uniformly added dropwise within 30 minutes, and the mixture was kept warm for 2 hours and then naturally cooled to room temperature, and a 32% sodium hydroxide solution was added to adjust the pH to 5, and the mixture was allowed to stand for 40 minutes and then filtered, and washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 40°C for 9 hours to obtain a carbon nanotube polycarboxylate water reducer;
[0047] (4) Aluminum isopropoxide and deionized water were mixed in a mass ratio of 1:2.2, stirred at 85°C and 150 rpm for 30 min, 0.38 times the mass of aluminum isopropoxide and 65% nitric acid solution and 0.2 times the mass of aluminum isopropoxide were added, the temperature was raised to 100°C, stirring was continued for 7 h, distilled for 25 min, a ball was dropped into an oil ammonia column with a disposable dropper, and the ball was poured out after standing for 2.5 h, washed with isopropanol 4 times, dried at 25°C for 24 h, and dried at 110°C for 8 h, moved to a muffle furnace, heated to 600°C at a rate of 3°C / min, calcined for 4 h, cooled naturally to room temperature, ground and sieved through 250 mesh to obtain spherical porous nano-alumina;
[0048] (5) Mix silicate cement and sand in a mass ratio of 1:3, stir at 25°C and 60 rpm for 2 min, add spherical porous nano-alumina (0.03 times the mass of silicate cement) and 0.5% polyethylene glycol (0.0015 times the mass of silicate cement), continue stirring for 2 min, add carbon nanotube polycarboxylate water reducer (0.04 times the mass of silicate cement) and deionized water (0.45 times the mass of silicate cement), continue stirring at 550 rpm for 15 min, and let stand for 2 min to obtain nano-ceramic slurry.
[0049] Example 3
[0050] A method for preparing a nano-ceramic slurry, the method comprising the following steps:
[0051] (1) Potassium permanganate and 4.8% sulfuric acid solution were mixed at a mass ratio of 1:25, and ultrasonically dispersed for 35 minutes to obtain a mixed solution; carbon nanotubes and 4.8% sulfuric acid solution were mixed at a mass ratio of 1:65, and ultrasonically dispersed for 35 minutes, stirred at 900 r / min in an oil bath to 155° C., and the mixed solution with a mass of 63 times that of the carbon nanotubes was added at a uniform rate within 40 minutes, and the stirring was continued for 4 hours. After naturally cooling to room temperature, the mixture was filtered, and 35 times the mass of the carbon nanotubes was added. The oxidized carbon nanotubes were mixed with lithium aluminum tetrahydride and tetrahydrofuran in a mass ratio of 1:0.4:80, stirred at 25°C and 900r / min for 10h under a nitrogen environment, and then naturally cooled to room temperature, and then washed with tetrahydrofuran, a 4% hydrochloric acid solution and deionized water for 5 times, and dried at 85°C for 10h to obtain hydroxylated carbon nanotubes;
[0052] (2) Mix hydroxylated carbon nanotubes, pyridine and N,N-dimethylformamide in a mass ratio of 1:0.02:17, stir at 30°C and 200 rpm for 10 min under a nitrogen atmosphere, add allyl chloroacetate 4 times the mass of the hydroxylated carbon nanotubes, continue stirring for 25 min, heat to 45°C and continue stirring for 1 h, then filter, wash with N,N-dimethylformamide 5 times, and dry at 85°C for 3 h to obtain modified carbon nanotubes;
[0053] (3) acrylic acid, modified carbon nanotubes, ascorbic acid, mercaptoethanol and deionized water were mixed in a mass ratio of 1:3:0.02:0.005:5 to obtain a mixed monomer solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:6 to obtain an oxidant solution; 3-methylbut-3-enyl polyethylene glycol ether, γ-methacryloxypropyltrimethoxysilane and deionized water were mixed in a mass ratio of 1:0.8:7, and stirred at 45°C and 200 rpm for 25 min. , under a nitrogen atmosphere, a mixed monomer solution of 15 times the mass of 3-methylbut-3-enylpolyethylene glycol ether and an oxidant solution of 0.9 times the mass of 3-methylbut-3-enylpolyethylene glycol ether were uniformly added dropwise within 40 minutes, kept warm for 1 hour and then naturally cooled to room temperature, a 33% mass fraction of sodium hydroxide solution was added to adjust the pH to 6, and the mixture was filtered after standing for 45 minutes, washed with deionized water and anhydrous ethanol for 5 times respectively, and dried at 45°C for 8 hours to obtain a carbon nanotube polycarboxylic acid water reducer;
[0054] (4) Aluminum isopropoxide and deionized water were mixed in a mass ratio of 1:2.3, stirred at 90°C and 200 rpm for 25 min, 70% nitric acid solution with a mass fraction of 0.39 times the mass of aluminum isopropoxide and liquid paraffin with a mass fraction of 0.3 times the mass of aluminum isopropoxide were added, the temperature was raised to 105°C, stirring was continued for 6 h, distilled for 20 min, a ball was dropped into an oil ammonia column with a disposable dropper, the ball was poured out after standing for 3 h, washed with isopropanol 5 times, dried at 30°C for 23 h, dried at 115°C for 7 h, moved to a muffle furnace, heated to 650°C at a rate of 4°C / min, calcined for 3 h, cooled naturally to room temperature, ground and sieved through 300 mesh to obtain spherical porous nano-alumina;
[0055] (5) Mix silicate cement and sand in a mass ratio of 1:4, stir at 30°C and 65 rpm for 1 min, add spherical porous nano-alumina (0.04 times the mass of silicate cement) and polyethylene glycol (0.6% by mass) (0.002 times the mass of silicate cement), continue stirring for 1 min, add carbon nanotube polycarboxylate water-reducing agent (0.05 times the mass of silicate cement) and deionized water (0.4 times the mass of silicate cement), continue stirring at 600 rpm for 10 min, and let stand for 1 min to obtain nano-ceramic slurry.
[0056] Comparative Example 1
[0057] A method for preparing a nano-ceramic slurry, the method comprising the following steps:
[0058] (1) Potassium permanganate and 4.7% sulfuric acid solution are mixed at a mass ratio of 1:24, and ultrasonically dispersed for 30 minutes to obtain a mixed solution; carbon nanotubes and 4.7% sulfuric acid solution are mixed at a mass ratio of 1:60, and ultrasonically dispersed for 30 minutes, stirred at 850 r / min in an oil bath to 150° C., and the mixed solution of 62.5 times the mass of the carbon nanotubes is added at a uniform rate within 35 minutes, and the stirring is continued for 5 hours. After naturally cooling to room temperature, the mixture is filtered, and a 24% hydrochloric acid solution of 30 times the mass of the carbon nanotubes is added. After standing for 5 minutes, the mixture is filtered, washed with deionized water for 4 times, and dried at 80° C. for 12 hours to obtain oxidized carbon nanotubes;
[0059] (2) The oxidized carbon nanotubes, pyridine and N,N-dimethylformamide were mixed in a mass ratio of 1:0.015:16.5, stirred at 25°C and 150 rpm for 15 min under a nitrogen atmosphere, and allyl chloroacetate (3.5 times the mass of the oxidized carbon nanotubes) was added, and the stirring was continued for 30 min. The temperature was raised to 40°C and the stirring was continued for 2 h. After filtering, the mixture was washed with N,N-dimethylformamide 4 times, and dried at 80°C for 3.5 h to obtain modified carbon nanotubes;
[0060] (3) acrylic acid, modified carbon nanotubes, ascorbic acid, mercaptoethanol and deionized water were mixed in a mass ratio of 1:2.5:0.015:0.004:4 to obtain a mixed monomer solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:5 to obtain an oxidant solution; 3-methylbut-3-enyl polyethylene glycol ether, γ-methacryloxypropyltrimethoxysilane and deionized water were mixed in a mass ratio of 1:0.7:6, and stirred at 40°C and 150 rpm for 30 min. n, under a nitrogen atmosphere, a mixed monomer solution of 14 times the mass of 3-methylbut-3-enylpolyethylene glycol ether and an oxidant solution of 0.8 times the mass of 3-methylbut-3-enylpolyethylene glycol ether were uniformly added dropwise within 30 minutes, and the mixture was kept warm for 2 hours and then naturally cooled to room temperature, and a 32% sodium hydroxide solution was added to adjust the pH to 5, and the mixture was allowed to stand for 40 minutes and then filtered, and washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 40°C for 9 hours to obtain a carbon nanotube polycarboxylate water reducer;
[0061] (4) Aluminum isopropoxide and deionized water were mixed in a mass ratio of 1:2.2, stirred at 85°C and 150 rpm for 30 min, 0.38 times the mass of aluminum isopropoxide and 65% nitric acid solution and 0.2 times the mass of aluminum isopropoxide were added, the temperature was raised to 100°C, stirring was continued for 7 h, distilled for 25 min, a ball was dropped into an oil ammonia column with a disposable dropper, and the ball was poured out after standing for 2.5 h, washed with isopropanol 4 times, dried at 25°C for 24 h, and dried at 110°C for 8 h, moved to a muffle furnace, heated to 600°C at a rate of 3°C / min, calcined for 4 h, cooled naturally to room temperature, ground and sieved through 250 mesh to obtain spherical porous nano-alumina;
[0062] (5) Mix silicate cement and sand in a mass ratio of 1:3, stir at 25°C and 60 rpm for 2 min, add spherical porous nano-alumina (0.03 times the mass of silicate cement) and 0.5% polyethylene glycol (0.0015 times the mass of silicate cement), continue stirring for 2 min, add carbon nanotube polycarboxylate water reducer (0.04 times the mass of silicate cement) and deionized water (0.45 times the mass of silicate cement), continue stirring at 550 rpm for 15 min, and let stand for 2 min to obtain nano-ceramic slurry.
[0063] Comparative Example 2
[0064] A method for preparing a nano-ceramic slurry, the method comprising the following steps:
[0065] (1) Potassium permanganate and 4.7% sulfuric acid solution were mixed at a mass ratio of 1:24, and ultrasonically dispersed for 30 minutes to obtain a mixed solution; carbon nanotubes and 4.7% sulfuric acid solution were mixed at a mass ratio of 1:60, and ultrasonically dispersed for 30 minutes, stirred at 850 r / min in an oil bath to 150° C., and 62.5 times the mass of the carbon nanotubes were added to the mixed solution at a constant rate within 35 minutes, and the stirring was continued for 5 hours. After naturally cooling to room temperature, the mixture was filtered, and 30 times the mass of the carbon nanotubes were added. A 24% hydrochloric acid solution was allowed to stand for 5 minutes, then filtered, washed with deionized water for 4 times, and dried at 80°C for 12 hours to obtain oxidized carbon nanotubes; the oxidized carbon nanotubes, lithium aluminum tetrahydride and tetrahydrofuran were mixed in a mass ratio of 1:0.35:75, stirred at 20°C and 850r / min for 12 hours under a nitrogen environment, cooled naturally to room temperature, washed with tetrahydrofuran, a 3.5% hydrochloric acid solution and deionized water for 4 times, and dried at 80°C for 12 hours to obtain hydroxylated carbon nanotubes;
[0066] (2) Mix hydroxylated carbon nanotubes, pyridine and N,N-dimethylformamide in a mass ratio of 1:0.015:16.5, stir for 15 min at 25 ° C and 150 rpm under a nitrogen atmosphere, add allyl chloroacetate (3.5 times the mass of hydroxylated carbon nanotubes), continue stirring for 30 min, heat to 40 ° C and continue stirring for 2 h, filter, wash with N,N-dimethylformamide 4 times, and dry at 80 ° C for 3.5 h to obtain modified carbon nanotubes;
[0067] (3) acrylic acid, modified carbon nanotubes, ascorbic acid, mercaptoethanol and deionized water were mixed in a mass ratio of 1:2.5:0.015:0.004:4 to obtain a mixed monomer solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:5 to obtain an oxidant solution; 3-methylbut-3-enyl polyethylene glycol ether and deionized water were mixed in a mass ratio of 1:0.7:6, and stirred at 40°C and 150 rpm for 30 min under a nitrogen atmosphere. A mixed monomer solution of 14 times the mass of 3-methylbut-3-enylpolyethylene glycol ether and an oxidant solution of 0.8 times the mass of 3-methylbut-3-enylpolyethylene glycol ether were uniformly added dropwise within 30 minutes, and the mixture was naturally cooled to room temperature after being kept warm for 2 hours, and a sodium hydroxide solution with a mass fraction of 32% was added to adjust the pH to 5, and the mixture was filtered after standing for 40 minutes, and washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 40°C for 9 hours to obtain a carbon nanotube polycarboxylic acid water reducer;
[0068] (4) Aluminum isopropoxide and deionized water were mixed in a mass ratio of 1:2.2, stirred at 85°C and 150 rpm for 30 min, 0.38 times the mass of aluminum isopropoxide and 65% nitric acid solution and 0.2 times the mass of aluminum isopropoxide were added, the temperature was raised to 100°C, stirring was continued for 7 h, distilled for 25 min, a ball was dropped into an oil ammonia column with a disposable dropper, and the ball was poured out after standing for 2.5 h, washed with isopropanol 4 times, dried at 25°C for 24 h, and dried at 110°C for 8 h, moved to a muffle furnace, heated to 600°C at a rate of 3°C / min, calcined for 4 h, cooled naturally to room temperature, ground and sieved through 250 mesh to obtain spherical porous nano-alumina;
[0069] (5) Mix silicate cement and sand in a mass ratio of 1:3, stir at 25°C and 60 rpm for 2 min, add spherical porous nano-alumina (0.03 times the mass of silicate cement) and 0.5% polyethylene glycol (0.0015 times the mass of silicate cement), continue stirring for 2 min, add carbon nanotube polycarboxylate water reducer (0.04 times the mass of silicate cement) and deionized water (0.45 times the mass of silicate cement), continue stirring at 550 rpm for 15 min, and let stand for 2 min to obtain nano-ceramic slurry.
[0070] Comparative Example 3
[0071] A method for preparing a nano-ceramic slurry, the method comprising the following steps:
[0072] (1) Potassium permanganate and 4.7% sulfuric acid solution were mixed at a mass ratio of 1:24, and ultrasonically dispersed for 30 minutes to obtain a mixed solution; carbon nanotubes and 4.7% sulfuric acid solution were mixed at a mass ratio of 1:60, and ultrasonically dispersed for 30 minutes, stirred at 850 r / min in an oil bath to 150° C., and 62.5 times the mass of the carbon nanotubes were added to the mixed solution at a constant rate within 35 minutes, and the stirring was continued for 5 hours. After naturally cooling to room temperature, the mixture was filtered, and 30 times the mass of the carbon nanotubes were added. A 24% hydrochloric acid solution was allowed to stand for 5 minutes, then filtered, washed with deionized water for 4 times, and dried at 80°C for 12 hours to obtain oxidized carbon nanotubes; the oxidized carbon nanotubes, lithium aluminum tetrahydride and tetrahydrofuran were mixed in a mass ratio of 1:0.35:75, stirred at 20°C and 850r / min for 12 hours under a nitrogen environment, cooled naturally to room temperature, washed with tetrahydrofuran, a 3.5% hydrochloric acid solution and deionized water for 4 times, and dried at 80°C for 12 hours to obtain hydroxylated carbon nanotubes;
[0073] (2) Mix hydroxylated carbon nanotubes, pyridine and N,N-dimethylformamide in a mass ratio of 1:0.015:16.5, stir for 15 min at 25 ° C and 150 rpm under a nitrogen atmosphere, add allyl chloroacetate (3.5 times the mass of hydroxylated carbon nanotubes), continue stirring for 30 min, heat to 40 ° C and continue stirring for 2 h, filter, wash with N,N-dimethylformamide 4 times, and dry at 80 ° C for 3.5 h to obtain modified carbon nanotubes;
[0074] (3) acrylic acid, modified carbon nanotubes, ascorbic acid, mercaptoethanol and deionized water were mixed in a mass ratio of 1:2.5:0.015:0.004:4 to obtain a mixed monomer solution; ammonium persulfate and deionized water were mixed in a mass ratio of 1:5 to obtain an oxidant solution; 3-methylbut-3-enyl polyethylene glycol ether, γ-methacryloxypropyltrimethoxysilane and deionized water were mixed in a mass ratio of 1:0.7:6, and stirred at 40°C and 150 rpm for 30 min. n, under a nitrogen atmosphere, a mixed monomer solution of 14 times the mass of 3-methylbut-3-enylpolyethylene glycol ether and an oxidant solution of 0.8 times the mass of 3-methylbut-3-enylpolyethylene glycol ether were uniformly added dropwise within 30 minutes, and the mixture was kept warm for 2 hours and then naturally cooled to room temperature, and a 32% sodium hydroxide solution was added to adjust the pH to 5, and the mixture was allowed to stand for 40 minutes and then filtered, and washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 40°C for 9 hours to obtain a carbon nanotube polycarboxylate water reducer;
[0075] (4) Mix silicate cement and sand in a mass ratio of 1:3, stir at 25°C and 60 rpm for 2 min, add 0.03 times the mass of silicate cement nano-alumina and 0.5% polyethylene glycol (mass fraction) ...) (mass fraction) (mass fraction))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))
[0076] Effect example
[0077] Table 1 below shows the analysis results of the crack resistance, compression resistance and durability of the nano-ceramic slurries of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.
[0078] Table 1
[0079] Splitting tensile strength MPa Compressive strength MPa Relative dynamic modulus loss rate % Example 1 4.9 65.7 1.5 Example 2 5.2 68.3 1.4 Example 3 5.1 64.1 1.7 Comparative Example 1 2.4 63.5 1.9 Comparative Example 2 4.7 64.2 3.3 Comparative Example 3 4.3 42.3 2.1
[0080] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the nano-ceramic slurry prepared by the present invention has good crack resistance, compression resistance and durability.
[0081] By comparison, the splitting tensile strength of Examples 1, 2, and 3 is higher than that of Example 1, which indicates that the carboxyl groups on the surface of the oxidized carbon nanotubes are reduced to hydroxyl groups, thereby improving the subsequent grafting efficiency of allyl chloroacetate, so as to carry out in-situ polymerization on the carbon nanotubes to generate polycarboxylic acid organic macromolecules, enhance the dispersibility and dispersion stability of the carbon nanotubes, and improve the crack resistance of the nano-ceramic slurry; by comparison, the relative dynamic modulus loss rate of Examples 1, 2, and 3 is lower than that of Example 2, which indicates that the introduction of γ-methacryloxypropyltrimethoxysilane for copolymerization increases the adsorption amount of the water reducer molecules in the nano-ceramic slurry, reduces the permeability and water absorption of the nano-ceramic slurry, and improves the durability of the nano-ceramic slurry; by comparison, the compressive strength of Examples 1, 2, and 3 is higher than that of Example 3, and the relative dynamic modulus loss rate is lower, which indicates that doping with spherical porous nano-alumina can fill the pores in the slurry, improve the microstructure of the slurry, and enhance the compressive resistance of the nano-ceramic slurry through the strengthening effect.
[0082] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a nano-ceramic slurry, characterized in that: The method comprises the following preparation steps: (1) Potassium permanganate and 4.6-4.8% sulfuric acid solution were mixed at a mass ratio of 1:(23-25), and ultrasonically dispersed for 25-35 min to obtain a mixed solution; carbon nanotubes and 4.6-4.8% sulfuric acid solution were mixed at a mass ratio of 1:(55-65), and ultrasonically dispersed for 25-35 min. The mixture was stirred at 800-900 r / min in an oil bath to 145-155°C, and 62-63 times the mass of the carbon nanotubes was added at a uniform rate within 30-40 min. The mixture was stirred for 4-6 h, and the mixture was naturally cooled to room temperature and filtered. Then, 25-35 times the mass of the carbon nanotubes was added. A hydrochloric acid solution with a mass fraction of 23-25% is allowed to stand for 4-6 minutes, then filtered, washed with deionized water for 3-5 times, and dried at 75-85°C for 11-13 hours to obtain oxidized carbon nanotubes; the oxidized carbon nanotubes, lithium aluminum tetrahydride and tetrahydrofuran are mixed in a mass ratio of 1: (0.3-0.4): (70-80), stirred at 800-900r / min for 10-14 hours at 15-25°C in a nitrogen environment, and cooled naturally to room temperature, and then washed with tetrahydrofuran, a hydrochloric acid solution with a mass fraction of 3-4% and deionized water for 3-5 times, respectively, and dried at 75-85°C for 10-14 hours to obtain hydroxylated carbon nanotubes; (2) Mix hydroxylated carbon nanotubes, pyridine and N,N-dimethylformamide in a mass ratio of 1:(0.01-0.02):(16-17), stir at 100-200 rpm for 10-20 min at 20-30 °C under a nitrogen atmosphere, add allyl chloroacetate in an amount of 3-4 times the mass of the hydroxylated carbon nanotubes, continue stirring for 25-35 min, heat to 35-45 °C, continue stirring for 1-3 h, filter, wash with N,N-dimethylformamide 3-5 times, and dry at 75-85 °C for 3-4 h to obtain modified carbon nanotubes; (3) Acrylic acid, modified carbon nanotubes, ascorbic acid, mercaptoethanol and deionized water were mixed in a mass ratio of 1:(2-3):(0.01-0.02):(0.003-0.005):(3-5) to obtain a mixed monomer solution; 3-methylbut-3-enyl polyethylene glycol ether, γ-methacryloxypropyltrimethoxysilane and deionized water were mixed in a mass ratio of 1:(0.6-0.8):(5-7), stirred at 35-45°C and 100-200 rpm for 25-35 min, and incubated in a nitrogen atmosphere. Under the environment, a mixed monomer solution of 13 to 15 times the mass of 3-methylbut-3-enyl polyethylene glycol ether and an oxidant solution of 0.7 to 0.9 times the mass of 3-methylbut-3-enyl polyethylene glycol ether are uniformly added dropwise within 20 to 40 minutes, and the mixture is kept warm for 1 to 3 hours and then naturally cooled to room temperature, and a sodium hydroxide solution with a mass fraction of 31 to 33% is added to adjust the pH to 4 to 6, and the mixture is allowed to stand for 35 to 45 minutes, and the mixture is washed with deionized water and anhydrous ethanol for 3 to 5 times respectively, and dried at 35 to 45° C. for 8 to 10 hours to obtain a carbon nanotube polycarboxylic acid water reducer; (4) Mix aluminum isopropoxide and deionized water in a mass ratio of 1:(2.1-2.3), stir at 80-90°C and 100-200 rpm for 25-35 min, add 0.37-0.39 times the mass of aluminum isopropoxide and 60-70% nitric acid solution and 0.1-0.3 times the mass of aluminum isopropoxide, add liquid paraffin, heat to 95-105°C, continue stirring for 6-8 h, and distill for 20-3 0min, drop the ball into the oil-ammonia column with a disposable dropper, pour it out after standing for 2~3h, wash it with isopropanol 3~5 times, dry it at 20~30℃ for 23~25h, dry it at 105~115℃ for 7~9h, move it into a muffle furnace, heat it to 550~650℃ at a rate of 2~4℃ / min, calcine it for 3~5h, cool it naturally to room temperature, grind and sieve 200~300 mesh to obtain spherical porous nano-alumina; (5) Mix silicate cement and sand in a mass ratio of 1:(2-4), stir at 20-30°C and 55-65 rpm for 1-3 min, add spherical porous nano-alumina (0.02-0.04 times the mass of silicate cement) and polyethylene glycol (0.4-0.6% by mass) (0.001-0.002 times the mass of silicate cement), continue stirring for 1-3 min, add carbon nanotube polycarboxylate water-reducing agent (0.03-0.05 times the mass of silicate cement) and deionized water (0.4-0.5 times the mass of silicate cement), continue stirring at 500-600 rpm for 10-20 min, let stand for 1-3 min, and obtain nano-ceramic slurry.
2. The method for preparing a nano-ceramic slurry according to claim 1, characterized in that: The reaction equation for the hydroxylation of carbon nanotubes in step (1) is: 。 3. The method for preparing a nano-ceramic slurry according to claim 1, characterized in that: The reaction equation for modifying the carbon nanotubes in step (2) is: 。 4. The method for preparing a nano-ceramic slurry according to claim 1, characterized in that: The oxidant solution in step (3) is obtained by mixing ammonium persulfate and deionized water in a mass ratio of 1:(4-6).
5. A nano-ceramic slurry prepared according to the method for preparing a nano-ceramic slurry according to any one of claims 1 to 4.
Citation Information
Patent Citations
Method for preparing high-toughness ceramic mold material
CN106316368A
Preparation method of carbon nanotube reinforced alumina-based composite material
CN109081684A